Comparison of clinical safety of minimal access surgery/laparoscopy versus open surgery in terms of patient outcomes and risk to theatre staff during the COVID-19 pandemic - Zargar, Owais-Ul-Umer; Albina, Ayat; Albina, Ayat; Ashraf, Nashrah; Ashraf, Nashrah; Iqbal, Javed; Iqbal, Javed; Dhingra, N. C.; Dhingra, N. C. (International Journal of Research in Medical Sciences, 2022)
Background: The COVID-19 pandemic has greatly affected surgical practice in all parts of the world because the safety of minimal access surgery (MAS) was questioned during the COVID-19 pandemic due to increased concern with regard to disease spread. This study assessed the available evidence on the safety of laparoscopy as compared to open surgery during the COVID-19, explored the possible precautions to be taken to prevent exposure of the operating team to the viral infection. The objective of this study was to access the clinical safety of laparoscopy as compared to open surgery during the COVID-19 pandemic. Methods: This study was a retrospective study conducted during the COVID-19 pandemic in the Department of Surgery, GMC, India, from January 2020 to January 2021. The various outcomes assessed included: burden of covid-19 infection among the patients, deaths due to COVID-19, infection acquired by staff, length of hospital stay and post-discharge symptomatology among patients. Results: There was no statistically significant difference in terms of median age of patients (p=0.853), gender (p=0.835), American Society of Anesthesiologists (ASA) status (p=0.876), urgency of operation (p=0.074), total time in theatre complex (p=0.163) or total number of theatre staff involved (p=0.831). The length of stay in the hospital was significantly shorter in the laparoscopic as compared the open group (3.5 versus 9 days; p=0.011). Conclusions: Based on our review, we concluded that if recommended guidelines are followed and proper precautions are taken, laparoscopic surgery is safe for patients and theatre staff during the COVID-19 pandemic. Only on the basis of COVID-19, laparoscopy should not be replaced by laparotomy. If laparoscopy is strongly indicated in patients, it can be used with precautions because of its benefits over open surgery.